Verbal Violence In Picky Picks Youtube Channel - Pratiwi, Diana Aprilia; Nurhayati, Iis Kurnia (eProceedings of Management, 2024)
The internet is employed as a community communication tools, along with the emergence of new media as a communication medium in today’s global society. In recent years, Indonesia have been more interested in using the internet. According to databoks.katadata.co.id, there were 204.7 million internet users in Indonesia in Januari 2022. Social media has become an indispensable tool for carrying out daily tasks. Social media is utilized as a place to express oneself in addition to being an important platform for business and marketing. YouTube is one of the social media that offers a video gateway as an alternative for the public to watch internet-based digital shows. The purpose of this study was to find out representation verbal violence in reaction content on video on YouTube channel Picky Picks. The research method used in this study is a quantitative research techniques. The researcher used two coders to ensure objectivity in coding and data collecting. Two encoders are used to assess the authenticity of the data collected and determine the correctness of the data using a reliability tet is utilized to determine the data’s accuracy. The results show The intensity of verbal violence in the promotional video on the Picky Picks YouTube channel shows a significant amount. From the entire sample of videos studied, the euphemism category ranks first as verbal violence that appears most often in Picky Picks video with 33 times or 39,1%. Therefore, most verbal violence contained in the video on Picky Picks YouTube channel is a euphemism. In the second position, the verbal violence often used by Picky Picks’s video is dysphemism. The conclusion of this study shows for the government should be more active in controlling YouTube channels that have similar content with research, by blocking and ensnaring channel creators on YouTube who have harmful content, with the previously discussed law, namely the ITE Law (Information and Electronic Transactions). To prevent the proliferation of these Youtube channels which can damage the morale of society. For readers, with the research that has been made, hopefully, it will be an additional insight and prefer the Youtube channel as entertainment. Keywords-verbal violence, reaction content, YouTube